STUDI PENGARUH INTERKONEKSI GARDU INDUK 150 kV CENDANA 30 MVA TERHADAP RUGI-RUGI PADA JARINGAN TRANSMISI SISTEM KHATULISTIWA - Gunawan, -; -, Purwoharjono; Abidin, Zainal (Faculty of Engineering, Universitas Tanjungpura, 2022)
The electrical power interconnection system is a system consisting of several power generating centers and several substations (GI) which are connected to each other through a transmission line and serve all the loads on the GI connected to the distribution system. This study will compare the power flow losses in conditions before and after the Khatulistiwa system is connected. The method used to analyze the results of the power flow calculation to determine how much the losses during the conditions before and after interconnection include the Newton-Rapshon method. With the GI interconnectio Cendana on the Khatulistiwa System, then there is an additional 1 bus, namely bus 16 (GI. Cendana). In the existing Khatulistiwa System, the total active and reactive power generation is 351.044 MW and -57.559 MVAr, while the active and reactive power losses are 9.944 MW and 54.341 MVAr. After GI interconnection. Sandalwood in the Khatulistiwa System produces a total active and reactive power generation of 351.037 MW and -27.589 MVAr, while the active and reactive power losses are 9.937 MW and 54.312 MVAr. With the GI interconnection. Cendana, the 150 kV Khatulistiwa System bus voltage did not change (fixed) because the power flow analysis was carried out on a high voltage system so that it obtained a small voltage drop.